The direct use of mobile phone and the occurrence of chondrodermatitis nodularis in the antihelix: An exemplificative case - Federica Di Berardino; Diego Zanetti (Wolters Kluwer Medknow Publications, 2018)
Chondrodermatitis nodularis helicis (CNH) is an idiopathic inflammatory painful condition of the ear characterized by a tender nodule located on the helix or antihelix. Even if various causes have been ascribed, such as a microvascular injury due to acute exposure to cold or trauma, pressure, or rubbing, etiopathogenesis still remains unknown. We describe the unusual case of a young female with a peculiar sequential onset of bilateral CNH in the antihelix region, possibly ascribed to the direct use of mobile phone without earphones.